2017
DOI: 10.1073/pnas.1700455114
|View full text |Cite
|
Sign up to set email alerts
|

Stress-inducible gene Atf3 in the noncancer host cells contributes to chemotherapy-exacerbated breast cancer metastasis

Abstract: Chemotherapy is a double-edged sword. It is anticancer because of its cytotoxicity. Paradoxically, by increasing chemoresistance and cancer metastasis, it is also procancer. However, the underlying mechanisms for chemotherapy-induced procancer activities are not well understood. Here we describe the ability of paclitaxel (PTX), a frontline chemotherapeutic agent, to exacerbate metastasis in mouse models of breast cancer. We demonstrate that, despite the apparent benefit of reducing tumor size, PTX increased th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
191
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 143 publications
(198 citation statements)
references
References 79 publications
(104 reference statements)
6
191
0
1
Order By: Relevance
“…Chemotherapy-induced TMEM assembly and metastasis has been further corroborated by another research group using multiple models of breast carcinoma [6].…”
Section: George S Karagiannis John S Condeelis and Maja H Oktaymentioning
confidence: 70%
See 2 more Smart Citations
“…Chemotherapy-induced TMEM assembly and metastasis has been further corroborated by another research group using multiple models of breast carcinoma [6].…”
Section: George S Karagiannis John S Condeelis and Maja H Oktaymentioning
confidence: 70%
“…paclitaxel) and non-taxane (i.e doxorubicin and cyclophosphamide) chemotherapies [3]. Accordingly, Editorial stress-inducible genes, such as cyclic AMP-dependent transcription factor ATF3, appear to be non-cancer cell-associated master orchestrators of chemotherapyexacerbated breast cancer metastasis [6], further confirming a more generalized cytotoxic mechanism behind the chemotherapy-induced pro-metastatic phenotype. However, other researchers have indicated that certain chemotherapeutic drugs (e.g.…”
Section: George S Karagiannis John S Condeelis and Maja H Oktaymentioning
confidence: 92%
See 1 more Smart Citation
“…Recent published work by Karagiannis and collaborators (Karagiannis, Pastoriza et al 2017), and Chang and colleagues (Chang, Jalgaonkar et al 2017) show that though neoadjuvant chemotherapy reduces tumor size, they also increase breast tumor metastasis. Karagiannis, et al using intra-vital imaging show that paclitaxel treated mice have greater vascular leakage and tumor cell dissemination, which occurs from specific site, which they define as the tumor microenvironment of metastasis (TMEM) site.…”
mentioning
confidence: 98%
“…Although neoadjuvant therapy can reduce tumor size to nondistinguishable levels it does not improve overall patient survival (Rastogi, Anderson et al 2008, Gianni, Baselga et al 2009). This paradox is answered by new findings from Karagiannis and collaborators (Karagiannis, Pastoriza et al 2017), and Chang and colleagues (Chang, Jalgaonkar et al 2017) who show that though neoadjuvant chemotherapy reduces tumor size, they also increase breast tumor metastasis. …”
mentioning
confidence: 99%